Colostomy for Perianal Sepsis With Ecthyma Gangrenosum in Immunocompromised Children. Issue 1 (January 2016) - Vuille-dit-Bille, Raphael N.; Berger, Christoph; Meuli, Martin; Grotzer, Michael A.
Abstract : Background: Perianal sepsis with ecthyma gangrenosum is a severe and potentially mutilating complication in immunocompromised children. Therapies include antimicrobial treatment, incision and drainage, generous tissue debridement, and skin transplantation. Procedure: We describe 3 children with acute lymphoblastic leukemia having sepsis with Pseudomonas aeruginosa in febrile neutropenia and severe perianal infections treated relatively early with a protective colostomy. Indications for colostomy were nonhealing wounds, and ceaseless pain. Results: All patients showed a rapid reduction of pain. Complete wound healing was seen in 2 patients, and considerable pain reduction and increased quality of life were seen in a third patient during palliative care. Conclusions: These results suggest that a protective colostomy should be considered early in the management of immunocompromised children with ecthyma gangrenosum.